ADMINISTRATIVE REFORM AND ITS IMPACT ON ACHIEVING THE MENTAL IMAGE OF THE ORGANIZATION (A CASE STUDY OF AL-FURAT AL-AWSAT TECHNICAL UNIVERSITY) (World Economics and Finance Bulletin, 2022)
This research deals with the concept of administrative reform, which is one of the most important scientific concepts that accommodate proposals in various sciences, including management, sociology, psychology and other sciences.The aim of the research is to reveal the extent of the interest of the Middle Euphrates Technical University, the research sample, which is considered one of the government technical universities in Iraq, to support administrative reform in its three dimensions (service quality, creativity and innovation, and technology) and its impact on achieving a positive mental image of its university services, which it seeks to develop every One of the administrative and academic leaders at the researched university.The research found that there is a growing interest from the researched university in supporting the administrative reform of university services. As this is evident in the administrative interest, considering the entry of the Middle Euphrates Technical University in the international rankings as an indicator ofthe quality of technical education, the power of knowledge is the ability of minds that produce it and put it into practice to improve and develop the internal community of the university in question, and elevate it forward to the ladder of development and Innovation
Keywords: Administrative reform; the mental image